2018
DOI: 10.1186/s12962-018-0127-6
|View full text |Cite|
|
Sign up to set email alerts
|

HTA and MCDA solely or combined? The case of priority-setting in Colombia

Abstract: BackgroundAll healthcare systems face problems of justice and efficiency related to setting priorities for allocating limited financial resources. Therefore, explicit decision-making in healthcare depicted as a continuum from evidence generation to deliberation and communication of the decision made, needs to be transparent and fair. Nevertheless, priority-setting in many parts of the world remains being implicit and ad-hoc process. Health Technology Assessment (HTA) and Multi-Criteria Decision Analysis (MCDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…MCDA is being considered and, in many cases, implemented within international HTA agencies as a mechanism to support transparent, robust, and equitable decision-making as well as in various other decision contexts (e.g., priority setting, clinical decision-making, etc.) [10,15,[19][20][21][22][23]. In Canada, value assessment frameworks have been developed to assess the value of oncology therapeutics being funded through public drug programs [24,25].…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…MCDA is being considered and, in many cases, implemented within international HTA agencies as a mechanism to support transparent, robust, and equitable decision-making as well as in various other decision contexts (e.g., priority setting, clinical decision-making, etc.) [10,15,[19][20][21][22][23]. In Canada, value assessment frameworks have been developed to assess the value of oncology therapeutics being funded through public drug programs [24,25].…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Following publication of this supplement article [ 1 ], the authors reported an error in the citation provided in the caption of Fig. 1.…”
Section: Correction To: Cost Eff Resour Alloc (2018) 16:47 101186/s1mentioning
confidence: 99%
“…• HTA lacks the ability to incorporate societal values into the decision-making process. HTA tends to slow down decisions due to restrictions generated by the appraisal, which in addition to negative reimbursement decisions hinder patients' access to health technologies, especially noted in cases of orphan drugs (Adkins, 2017;Aggarwal, 2014;Castro, 2018;Kido, 2019;Van Wilder, 2019;Yazdizadeh, 2018). • Negative reimbursement decision led to a strong resistance from clinicians (Schuller, 2017)…”
Section: Responsivenessmentioning
confidence: 99%
“…It generates cost saving through informing reimbursement and disinvestment decisions, which in the long-term improves technical, and allocative efficiency, as well as strategic pricing. HTA can contribute to budget control to ensure fiscal sustainability (Al-Aqeel, 2018;Angelis, 2018;Beletsi, 2018;Borges, 2018;Callea, 2017;Castro, 2018;Dabak, 2019;Dang, 2016;Epstein, 2020;Gagnon, 2014;Guthrie, 2015;Hailey, 2016;Hasegawa, 2020;Kanavos, 2019;Kido, 2019;Leelahavarong, 2019;Mahlich, 2017;Miquel-Cases, 2017;Nestler-Parr, 2018;Pearce, 2019;Schuller, 2017;Schumacher, 2013;Surgey, 2020;Tanvejsilp, 2019;Van Wilder, 2019;Vostalová, 2017;Yazdizadeh, 2018). • HTA improves pharmaceutical pricing, specially it ensures better value for money of orphan drugs (Kogushi, 2020;Mägi, 2018;Nestler-Parr, 2018;Roza, 2019;Vo, 2018).…”
Section: Fiscal Sustainability and Administrative Efficiencymentioning
confidence: 99%
See 1 more Smart Citation